Correlates of staff motivation, satisfaction, and job performance of library staff in selected Nigerian University libraries. Issue 1 (2nd March 2020) - Tella, Adeyinka; Ibinaiye, Olamide Abigail
Abstract: This study examined staff motivation, satisfaction, and job performance among the librarians and library staff in six selected university libraries in Nigeria. The target population for the study includes the professionals and nonprofessional library staff. A total enumeration sampling technique was used to select 180 respondents, which represent the sample for the study. Data was collected using a self-designed questionnaire titled "Staff Motivation, Satisfaction and Job Performance Questionnaire" (SMSJPQ). Six research questions were developed and answered by the study. The results indicate that librarian and library staff are highly motivated with regular pay while the least motivational factor is frequent interaction with their friends. Library staff are primarily satisfied with their jobs when they are in constant link with their friends. Professional library staff significantly experience better work motivation than their nonprofessional counterparts. Significant correlation exists between staff motivation and job performance and between job satisfaction and job performance. In addition, the two factors (motivation and satisfaction) exert significant contribution to the determinant of librarians and library staff job performance. Based on the findings, the study recommended improvement in the level of motivation of nonprofessionals so that the significant difference with the professional counterpart would not be so much pronounced.